Mekanisme Penyelesaian Tindak Pidana Penganiayaan Menurut Hukum Adat Lamaholot di Adonara Kabupaten Flores Timur - Natalia Tinsi Gita Sengaji; Karolus Kopong Medan; Ngongo Dede (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to identify the reasons why the Lamaholot indigenous community in Adonara Island, East Flores Regency, prefers to resolve assault crimes through customary law and to understand the settlement mechanism applied in the community. This research employed an empirical juridical method with a case approach. Data were collected through interviews, observations, and documentation, then analyzed descriptively using a qualitative approach. The results indicate that the Lamaholot community prefers customary law settlement due to the high level of trust in customary leaders, the fast, simple, and low-cost settlement process, as well as the strong values of kinship and social harmony within the community. In addition, the community’s belief in the moral and spiritual power of customary sanctions strengthens compliance with customary decisions. The settlement mechanism consists of several stages, namely reporting the case to customary leaders, summoning the disputing parties, conducting customary deliberations, reaching a peace agreement, and implementing customary sanctions such as customary fines, sacrificial animals, and the traditional oath known as tuak lolon goka. This settlement pattern reflects a restorative approach because it emphasizes the restoration of social relations and reconciliation between the offender and the victim. The study also shows that Lamaholot customary law is relevant to the concept of restorative justice within the national legal system, although challenges remain regarding the harmonization between customary law and positive law in Indonesia.